2023
DOI: 10.1111/aphw.12441
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of mindfulness‐based stress reduction (MBSR) on the mental health, HbA1C, and mindfulness of diabetes patients: A systematic review and meta‐analysis of randomised controlled trials

Abstract: The clinically standardised mindfulness-based stress reduction (MBSR) has been utilised as an intervention for improving mental health among diabetes patients The present study aimed to assess the effectiveness of mindfulness-based stress reduction (MBSR) on the mental health, haemoglobin A1c (HbA1C), and mindfulness of diabetes patients. A systematic review and meta-analysis approach was employed to review randomised controlled trials published in the English language between the inception of eight databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Mindfulness refers to the quality of being aware of the present moment with curious, open-minded, non-judging, non-striving, and acceptant attitudes (Kabat-Zinn, 1982 , 2013 ; Shapiro et al, 2008 ; Fisher et al, 2023 ). Mindfulness can provide cognitive flexibility to support the individual to actively construct current experiences and adapt to changing demands and challenging situations brought about by the COVID-19 pandemic by building mental resources and establishing new perspectives (Li et al, 2020 ).…”
mentioning
confidence: 99%
“…Mindfulness refers to the quality of being aware of the present moment with curious, open-minded, non-judging, non-striving, and acceptant attitudes (Kabat-Zinn, 1982 , 2013 ; Shapiro et al, 2008 ; Fisher et al, 2023 ). Mindfulness can provide cognitive flexibility to support the individual to actively construct current experiences and adapt to changing demands and challenging situations brought about by the COVID-19 pandemic by building mental resources and establishing new perspectives (Li et al, 2020 ).…”
mentioning
confidence: 99%
“…The integrated approach underlying the intervention is one of the elements that might have led to the positive impact observed in our preliminary data. Mindfulness-based interventions have been effective in enhancing quality of life and in mental health in different chronic conditions ( Demarzo et al, 2015 ; Crowe et al, 2016 ; Haller et al, 2017 ; Fisher et al, 2023 ) including MS ( Simpson et al, 2022 ). Both Mindfulness-Based Stress Reduction and Acceptance and Commitment Therapy (ACT) have yielded positive results on insomnia, fatigue, paresthesia, depression emotional competencies, and stress in people living with MS ( Sadeghi-Bahmani et al, 2022 ); however, a recent review unexpectedly did not find an improvement on quality of life after ACT ( Thompson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…During public health crises and future pandemics, these people will likely benefit from psychological interventions that enhance mindfulness, resilience, and self-efficacy to effectively reduce psychological distress. For example, mindfulness-based interventions (MBIs) have been proven to be effective in enhancing mindfulness and reducing mental distress (Fisher et al, 2023; Kabat-Zinn, 2003, 2013). The inclusion of mindfulness, resilience, and self-efficacy in the design and implementation of mental health intervention in response to future public health crisis may help mitigate some of the mental problems related to future pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…Keng et al's (2011) review of empirical studies found that trait mindfulness is negatively correlated with depression, social anxiety, negative affect, difficulties in emotion regulation, and negative automatic thoughts. Evidence from systematic reviews suggests that mindfulness-based interventions are efficacious for reducing mental distress (e.g., stress, anxiety, depression, posttraumatic stress disorder [PTSD]) in a wide range of populations, including children and adolescents (Kallapiran et al, 2015), pregnant women (Hall et al, 2016), and diabetes patients (Fisher et al, 2023;Ni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%